Antioxidant activity of yerba mate extracts: interactions between the individual polyphenols - Valerga, Julia (2013)
Yerba mate extracts contain strong antioxidants like chlorogenic (CL) and its derivatives, caffeic (C), quercetin (Q), rutin (R), and kaempferol (K) that may improve food products nutritional quality and rancidity. To obtain products with consistent activity and composition, we analyzed the effect of yerba’s industrial processing on extracts composition, radical scavenging capacity (AA), inhibition of b-carotene/ linoleic acid oxidation (AI), and ferric reducing/antioxidant power (RP). We also determined the relationship between the composition of a mixture of C, CL, K, Q, and R and their AA, RP, and AI values. Industrial processing modified polyphenol composition and antioxidant activity of the yerba extracts. Pre-dried and dried/canchada leaves were the most appropriate raw materials combining optimum AA, RP, and AI levels. Extract’s capacity to improve ground beef’s lipid stability was better than similar levels of a-tocopherol. Relationships between AA, RP, or AI and polyphenol composition were satisfactorily predicted by a quadratic, a full or a reduced cubic models, respectively. Simultaneous optimization of all models allowed determining the best and worst performing blends. Extracts contents of caffeic, chlorogenic and its derivatives, quercetin, and rutin were within or under the limits of the least active region predicted and may account for the low activity levels observed. Practical applications: Due to its antioxidant and therapeutic properties; polyphenolic extracts from yerba mate leaves can improve the sensorial quality and shelf life of ground beef and sunflower oil as well as enhance the organism defense system. Commercial application of these extracts by the food and pharmaceutical industry requires products of consistent composition and activity. In this study we also determined the best raw material across the different processing steps and developed mathematical models that can be used to calculate the antioxidant activity of yerba extracts based on their polyphenol composition.